Student Diversity and Differentiated Learning: Exploring Differentiated Learning Practices in Elementary Schools - Cahyanto, Bagus (Universitas Trunojoyo Madura, 2022)
One of the characteristics of learning in the independent curriculum is the application of differentiated learning, where this learning seeks to facilitate the needs and diversity of students in the class. This diversity can come from aspects of student learning styles, abilities, interests which will have an impact on the learning practices designed by the teacher. By implementing differentiated learning, the independent curriculum provides ample space for teachers to develop flexible and adaptive learning. This research aims to explore the implementation of differentiated learning in elementary schools. The researcher wants to reveal the practices carried out by teachers in facilitating student diversity at SDN 1 Ketindan, Malang Regency which focuses on differentiated learning practices. Researchers use a descriptive qualitative approach to explore and describe this phenomenon which emphasizes process, meaning and understanding to realize research objectives. Based on the research results, it shows that teachers have implemented differentiated learning well, content differentiation is carried out by teachers by differentiating content or material during learning. Teachers differentiate them by referring to the level of students' understanding of the material to be studied. Process differentiation is carried out by teachers by differentiating ways of delivering material to students which refers to their learning styles. Furthermore, the teacher carries out product differentiation by differentiating the learning products produced by students to see and measure students' mastery of the material they have studied.